A randomised trial of Mycobacterium w in critically ill patients with COVID-19: ARMY-1. Issue 2 (12th April 2021) - Sehgal, Inderpaul Singh; Guleria, Randeep; Singh, Sarman; Siddiqui, Mohammad Sabah; Agarwal, Ritesh
Purpose: We investigated whether Mycobacterium w ( Mw ), an immunomodulator, would improve clinical outcomes in coronavirus disease 2019 (COVID-19). Methods: We conducted an exploratory, randomised, double-blind, placebo-controlled trial of hospitalised subjects with severe COVID-19 (pulmonary infiltrates and oxygen saturation ≤94% on room air) conducted at four tertiary care centres in India. Patients were randomised 1:1 to receive either 0.3 mL·day −1 of Mw intradermally or a matching placebo for three consecutive days. The primary outcome of the study was the distribution of clinical status assessed on a seven-point ordinal scale ranging from discharged (category 1) to death (category 7) on study days 14, 21, and 28. The co-primary outcome was a change in SOFA (sequential organ failure assessment) score on days 7 and 14 compared to the baseline. The secondary outcomes were 28-day mortality, time to clinical recovery, time to reverse transcription PCR negativity, adverse events, and others. Results: We included 42 subjects (22 Mw, 20 placebo). On days 14 (OR 30.4 (95% CI 3.3–276.4)) and 21 (OR 14.9 (95% CI 1.8–128.4)), subjects in the Mw arm had a better clinical status distribution than placebo. There was no difference in the SOFA score change on days 7 and 14 between the two groups. We did not find any difference in the mortality, or other secondary outcomes. We observed no adverse events related to the use of Mw . Conclusions: The use of Mw results in better clinical status distribution on days 14 and 21 compared to placebo in critically ill patients with COVID-19. In this exploratory, multicentre, randomised, double-blind, placebo-controlled trial of 42 patients with severe #COVID19, a significantly better distribution of clinical status on days 14 and 21 was found for those randomised to the Mycobacterium w arm https://bit.ly/3q0sjOZ